Radar‐detected englacial debris in the West Antarctic Ice Sheet - Winter, Kate; Woodward, John; Ross, Neil; Dunning, Stuart A.; Hein, Andrew S.; Westoby, Matt; Culberg, Riley; Marrero, Shasta M.; Schroeder, Dustin M.; Sugden, David E.; Siegert, Martin J. (Geophysical Research Letters, 2019)
Structural glaci‐geological processes can entrain basal sediment into ice, leading to its transportation and deposition downstream. Sediments potentially rich in essential nutrients, like silica and iron, can thus be transferred from continental sources to the ocean, where deposition could enhance marine primary productivity. However, a lack of data has limited our knowledge of sediment entrainment, transfer and distribution in Antarctica, until now. We use ice‐penetrating radar to examine englacial sediments in the Weddell Sea sector of the West Antarctic Ice Sheet. Radargrams reveal englacial reflectors on the lee side of nunataks and subglacial highlands, where Mie scattering analysis of the reflectors suggests particle sizes consistent with surface moraine sediments. We hypothesize that these sediments aare entrained at the thermal boundary between cold and warm‐based ice. Conservative estimates of >130 x109 kg of englacial sediment in Horseshoe Valley alone suggest that the ice sheet has significant entrainment potential unappreciated previously.